Efektivitas pembelajaran daring dalam keterampilan membaca kreatif kelas v sekolah dasar - Ayyas Yahya; Rukayah Rukayah; Siti Kamsiyati (Didaktika Dwija Indria, 2022)
The purpose of this study was to determine the effectiveness of online learning on creative reading skills in fifth grade students of Menganti Elementary School, Sruweng District, Kebumen Regency. This research is a quantitative research. The research was conducted with one test. The research subjects were the fifth grade students of the Menganti State Elementary School, totaling 27 students. The data source came from students. Data collection techniques used questionnaires and multiple choice tests. The data validity and analysis the normality uses the person product moment through the SPSS 20.0 for windows application using the one-sample Kolmogorov-Smirnov technique. This research uses the approach applied is the Pre-experimental One Shot Case Study. The results showed that based on the Paired T-Test in the SPSS 20.0 application, the significance value (2-talled) of 0.061> 0.05 indicated that there was no significant difference between the results of the initial test scores and the results of the final test scores. This shows that there is no significant effect on the difference in treatment given to each variable. The conclusion of this study is that there is no effect on the effectiveness of online learning on the writing skills of fifth grade students at Menganti State Elementary School, Sruweng District, Kebumen Regency.